Kaedah al-istibra haiwan akuatik menurut perspektif Islam dan sains akuakultur : pangasius sutchii - Tengku Nor Hidayati, Tengku Zainal Abidin (2017)
Halal is the Islamic term that refers to something lawful or permissible. As such, undoubtedly halal animal can be consumed by Muslim once slaughtered properly according to Islamic teaching. However, in the case of halal animals that fed with contaminated food/filth (najis) continuously, the status of the animal according to majority of the scholars, is changed to al-jallālah. Animals fed with najasa are categorized as al-jallālah (contaminated animals) are only allowed to be consumed if they are quarantined for a certain period of time. Duration of quarantine varies according to the type of animals, that between one to forty days. During this quarantine period the animals will undergo a natural purification process or istiḥālah. Patin fish (pangasius sutchii) that is commonly consumed in Malaysia could be fed on najasa.like pig organs. During the quarantine or al-istibrā', natural purification process/istiḥālah will take place in fish digestive system. This study was carried out to estimate the istiḥālah period for patin fish after feeding with pig offal, based on the absence of DNA porcine in patin fish stomach and to suggest the sufficient period/time of istiḥālah for patin fish. Quarantine period is determined when there is completely no traces of DNA porcine from the fish. Detection of DNA porcine was done by using PCR and RT-PCR. The findings show detection of DNA porcine in fish stomach that fed pig organs, while DNA porcine was not detected on the skin and fish fillet during zero (0) hour quarantine period. After the 20 hours quarantine, DNA porcine was not detected in the stomach of the fish. The volume of water used varies between (20%, 50%, and 80%) for purification of patin from pig contamination. DNA porcine was not detected in the stomach of fish which were quarantined for 24 hours using the volume of water 20%, 50%, and 80%. Thus, the al-istibra‟ method can solve the issue of al-jallālah animals and further enhance the Malaysia aquaculture industry. Extraction of genomic DNA from tissue of different fish part, water and pig offal with the application of RNase A, improved the quality of DNA obtainded for most of molecular application based on the DNA purity. The total DNA yield is different among the sample this might be due to the different structure and compactness of the fish tissue.